Burkholderia Septicemia: A Case Report - Tarana Sarwat; Zarine Khan; Renu Dutta (Journal of Medical Sciences and Health, 2021)
Burkholderia cepacia is a bacterial pathogen which usually causes infection in immunocompromised or hospitalized patients. It also causes associated infections in patients with underlying pulmonary diseases, such as cystic fibrosis and chronic granulomatous diseases. It is often resistant to multiple antibiotics and has been found to grow even in medium containing penicillin. Here, we report a case of B. cepacia bacteremia in a post-operative patient of rheumatic heart disease with bilateral pleural effusion who, on being timely diagnosed, was managed effectively with appropriate antibiotics.